(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article informs the importance of family, community and education in educating the young generation in the spirit of military patriotism, as well as the idea that the education of today’s youth is one of the most responsible and urgent tasks, and the idea that the Motherland is one. It is about inculcating it in the minds and thinking of the rising generations.